Proclamation five interpreting the lessons of the church year - Reumann, John Henry Paul (Minneapolis Fortress Press, 1994)
Discuss appointed lessons for the 10th through 19th Sundays after Pentecost
"Overview of lectionary readings." p. 4-5
Keywords: Bible -- Homiletical use; Bible -- Liturgical lessons, English; Pentecost season -- Sermons -- Outlines, syllabi, etc